What Facial Appearance Reveals Over Time: When Perceived Expressions in Neutral Faces Reveal Stable Emotion Dispositions - Adams, Reginald B.; Garrido, Carlos O.; Albohn, Daniel N.; Hess, Ursula; Kleck, Robert E. (Frontiers in Psychology, 2016)
It might seem a reasonable assumption that when we are not actively using our faces to express ourselves (i.e., when we display nonexpressive, or neutral faces), those around us should not be able to read our emotions. Herein, using a variety of expression-related ratings, we examined whether age-related changes in the face can accurately reveal one’s innermost affective dispositions. In each study, we found that expressive ratings of neutral facial displays predicted self-reported positive/negative dispositional affect, but only for elderly women, and only for positive affect. These findings meaningfully replicate and extend earlier work examining age-related emotion cues in the face of elderly women (Malatesta, Fiore, & Messina, 1987). We discuss these findings in light of evidence that women are expected to, and do, smile more than men, and that the quality of their smiles predicts their life satisfaction. Although ratings of old male faces did not significantly predict self-reported affective dispositions, the trend was similar to that found for old female faces. A plausible explanation for this gender difference is that in the process of attenuating emotional expressions over their lifetimes, old men reveal less evidence of their total emotional experiences in their faces than do old women.